2012
DOI: 10.1186/1757-7241-20-85
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of traumatic cervical spine fractures: a prospective population study from Norway

Abstract: AimThe aim of this study was to estimate the incidence of traumatic cervical spine fractures (CS-fx) in a general population.BackgroundThe incidence of CS-fx in the general population is largely unknown.MethodsAll CS-fx (C0/C1 to C7/Th1) patients diagnosed with cervical-CT in Southeast Norway (2.7 million inhabitants) during the time period from April 27, 2010-April 26, 2011 were prospectively registered in this observational cohort study.ResultsOver a one-year period, 319 patients with CS-fx at one or more le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
74
4
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 40 publications
19
74
4
3
Order By: Relevance
“…Incomplete CSCIs have been reported to occur more often than complete CSCI. 6,10,17 Our finding was in line with these studies. It has also been reported that the percentage of incomplete CSCI is increasing, compared with complete CSCI.…”
Section: Level and Severity Of Injurysupporting
confidence: 83%
See 2 more Smart Citations
“…Incomplete CSCIs have been reported to occur more often than complete CSCI. 6,10,17 Our finding was in line with these studies. It has also been reported that the percentage of incomplete CSCI is increasing, compared with complete CSCI.…”
Section: Level and Severity Of Injurysupporting
confidence: 83%
“…Our findings show that fewer children and old individuals had CSCI compared with other age groups. Pickett et al 11 and Fredø et al 17 reported that the incidence of patients aged 460 years with CSCI was 26.5% and 54.5%, respectively, which are much higher than that observed in the present study (6.2%).…”
Section: The Proportion Of Tetraplegiacontrasting
confidence: 56%
See 1 more Smart Citation
“…Our findings documented that this trend has continued in the case of atlas fractures. Several studies find that simple falls are the most common causes of cervical fractures in the elderly [15][16][17][18][19]. One possible explanation for the increased incidence could be an increase in the number of falls in the elderly population.…”
Section: Increasing Incidence Of Atlas Fracturesmentioning
confidence: 99%
“…[8][9][10] Examples of these injuries include motor vehicle crashes, high impact accidents, explosions, and gunshots. [11][12][13] An acute injury to the cervical spine should be clinically diagnosable as work-related within 3 months of the injury.…”
Section: Cervical Conditions As Industrial Injuriesmentioning
confidence: 99%